Packaging specifications, puchasing, and quality control - Leonard, Edmund A. (Packaging and converting technology, 1996)
"Fourth Edition features four case histories of production and marketing problems caused by quality and communications gaps, a new perspective on the importance of bar coades, an updated and enlarged chapter on performance testing of unit loads and shipping regulations, new information on advanced flexible packaging, and more."